Possible Mechanisms of Relations between the Thermal Neutrons Field and Biosphere - Anton V. Syroeshkin; Irina V. Tarabrina; Mariya A. Morozova; Alla V. Marukhlenko; Igor A. Zlatskiy; Mariya P. Makarova (The Scientific World Journal)
This paper proposes some results concerning the interaction of living matter of different organization levels (prokaryotes and eukaryotes) with the flux of thermal neutrons. The phenomenon of the virtual neutron trap was tested during the passage of thermalized neutrons from the Pu-Be couple through a flat layer of E. coli suspension. We have studied the metabolic characteristics of A. salina cysts before and after artificial neutron flux exposure. It has been demonstrated that the concentrations of some metals in samples of alive and dead cysts irradiated with an artificial flow of thermal neutrons are not equal. The content of Mn in alive A. salina samples has increased more than ten-fold after their interaction with neutron flux, while the amount of As decreased by a factor of two after exposure. Levels of other elements (Al, Cr, Ni, Cu, Cd, and Pb) did not show any significant difference. Trace element composition of cysts was assessed using the method of atomic absorption spectroscopy with electrothermal atomization and the Zeeman background correction.